(untitled) (Research, Society and Development, 2022)
Bone tumors arising from the foot and ankle are relatively rare. The correct diagnosis is commonly ignored, and the potential risk of these tumors is often underestimated. Due to the rarity and particularities of the presentation, there is a lack of evidence on epidemiological data related to the distribution of bone tumors of the foot and ankle by age group, gender and location. As far as we know, no systematic review or meta-analysis was performed on the grouping of bone tumors in this region. The objective of this protocol is to design a systematic review of the evidence to verify these data. Systematic literature research will be carried out in the PubMed/MEDLINE, Embase (by CAPES JOURNALS) and LILACS databases, without time and linguistic restrictions in the search strategy. The reference lists of the included articles will be evaluated to detect unidentified studies. Two evaluators will independently select the articles, extract the data and assess the risk of bias in the selected studies. If applicable, meta-analysis will be carried out, extracting data for the number of events and total patients to perform proportion meta-analysis using the R software, with the "meta" package (version 4.9–6), the "metaprop function" for aspect ratio data. The results of this review will be added to the existing literature, providing convincing information on the epidemiology of these neoplasms, important data that will support future research and help in possible diagnostic, preventive and therapeutic measures. This protocol will provide a reliable theoretical basis for the research that will follow.